Differential Symbiodiniaceae Association With Coral and Coral-Eroding Sponge in a Bleaching Impacted Marginal Coral Reef Environment - Sambhaji Mote (Frontiers in Marine Science, 2021)
Marginal reefs are known for severe stress-inducible perturbations such as high sedimentation, eutrophication, ocean warming, and acidification from anthropogenic climate change. The corals striving in such stressful environments develop physiological adaptations induced by differential genomic expressions or association with thermal stress-tolerant algal symbionts (Symbiodiniaceae). Despite such adaptations, corals are threatened by other space competitors such as algae and sponges. Coral-eroding sponges belonging to the Cliona viridis complex are one such space competitors that also associate with Symbiodiniaceae algal photosymbiont. The diversity of Symbiodiniaceae associates with the coral and sponge from the same ecosystems is scarcely known. In the present study, Symbiodiniaceae community structure in the coral Turbinaria mesenterina, a newly described coral-eroding sponge Cliona thomasi, and their surrounding seawater was determined from the nearshore marginal reef along the central west coast of India. The results revealed a significantly higher relative abundance of Durusdinium and Gerakladium than Symbiodinium and Cladocopium in the seawater. Interestingly, both investigated host species showed differential Symbiodiniaceae association with significantly higher abundance of Durusdinium in coral and Gerakladium in sponge. The beta diversity analysis by Permutational multivariate analysis of variance (PERMANOVA) confirmed significant differences in Symbiodiniaceae profiles between sponge and coral. Durusdinium and Gerakladium are thermotolerant genera known to associate with different hosts in suboptimal conditions. Our field surveys suggested the bleaching resistance of the coral T. mesenterina despite the fact that the sea surface temperature reached the coral thermal threshold of 31°C during different periods of the years 2015, 2016, 2017, 2018, and 2019. Therefore, the thermal tolerance of the investigated coral and sponge species may be attributed to their respective thermotolerant photosymbiont associations. Furthermore, the results also indicated the host-specific photosymbiont selection from the local environment. Although these observations provide valuable biological insight, more research is needed to understand the tripartite association of sponge-coral-symbiont together to evaluate the competitive fitness of holobionts.